Visceral protein pool in highly skilled kayakers and canoeists - Makarova, G.; Pogrebnoy, A.; Chernuha, S.; Karpov, A. (Theory and Practice of Physical Culture, 2025)
Objective of the study is to assess the adequacy of delayed post-exercise recovery of total protein and albumin content in venous blood as criteria for visceral protein pool in highly skilled kayakers and canoeists.